Hydrothermal Syntheses and Crystal Structure of Hybrid Material Based on Keggin Cluster Modified by Nickel Complex - Zhang*, Y.N.; Zhang, Y.J.; Li, D.; Zhang, L.; Yang, M.; Liu, H. (Asian Journal of Chemistry, 2014)
A new organic-inorganic hybrid compound based on the Keggin polyoxometalates modified by nickel and N-ligand organic moiety: [Ni(phen)3]2[PMo11VIMoVO40] (1) (phen = 1,10-phenanthroline) has been hydrothermally synthesized and characterized structurally. It crystallizes in the triclinic space group P-1 with a = 12.203(2), b = 13.907(2), c = 14.438(3) Å; a = 104.859(2), b = 108.777(2), g = 93.376(2), V = 2215.3(7)Å3, C72H48N12O40PMo12Ni2, Mr = 3020.85, Z = 1, Dc = 2.264 g/cm3, m = 2.164 mm-1, F(000) = 1459, R = 0.0355 and wR = 0.0937 for 6948 observed reflections with I > 2s(I). The compound 1 consists of discrete polyoxoanions [PMo11VIMoVO40]4- and counter cations [Ni(phen)3]2+. The electrochemical property of compound 1 has been studied in the paper.